Think twice : communication activities for beginner to intermediate students, teacher's book - Hover, David (Cambridge : London : Cambridge University Press, 1986)
Think Twice consists of 39 activities which provide fluency practice for beginner to intermediate students of English. can be used alongside a coursebook or as revision. each activity focuses on one or two structures. wide-ranging and motivating topics. flexible in use, each activity being independent of the others.
Keywords: English language -- Study and teaching -- Foreign speakers